Synthetic DNA Assembly Using Golden Gate Cloning and the Hierarchical Modular Cloning Pipeline. Issue 1 (11th March 2020) - Marillonnet, Sylvestre; Grützner, Ramona
Abstract: Methods that enable the construction of recombinant DNA molecules are essential tools for biological research and biotechnology. Golden Gate cloning is used for assembly of multiple DNA fragments in a defined linear order in a recipient vector using a one‐pot assembly procedure. Golden Gate cloning is based on the use of a type IIS restriction enzyme for digestion of the DNA fragments and vector. Because restriction sites for the type IIS enzyme used for assembly must be present at the ends of the DNA fragments and vector but absent from all internal sequences, special care must be taken to prepare DNA fragments and the recipient vector with a structure suitable for assembly by Golden Gate cloning. In this article, protocols are presented for preparation of DNA fragments, modules, and vectors suitable for Golden Gate assembly cloning. Additional protocols are presented for assembly of defined parts in a transcription unit, as well as the stitching together of multiple transcription units into multigene constructs by the modular cloning (MoClo) pipeline. © 2020 The Authors. Basic Protocol 1 : Performing a typical Golden Gate cloning reaction Basic Protocol 2 : Accommodating a vector to Golden Gate cloning Basic Protocol 3 : Accommodating an insert to Golden Gate cloning Basic Protocol 4 : Generating small standardized parts compatible with hierarchical modular cloning (MoClo) using level 0 vectors Alternate Protocol : Generating large standardized parts compatible with hierarchical modular cloning (MoClo) using level –1 vectors Basic Protocol 5 : Assembling transcription units and multigene constructs using level 1, M, and P MoClo vectors